Application of 2DMPA method in develpoing fragility curves of plan-asymmetric structures. (15th December 2017) - Birzhandi, Mohammad S.; Halabian, Amir M.
Highlights: This study aimed to propose a procedure for the approximate and very fast IDA of plan-asymmetric structures using the 2DMPA method. This procedure can consider the hysteretic behavior of structures such as the pinching behavior, strength loss and stiffness deterioration. The median of intensity measures (IM) using 2DMPA-based fragility functions has +5.0% (over estimate) and −5.2% (under estimate) approximation in the worst case. This good estimation can be used for the fast estimation of collapse in the plan-asymmetric structures. Abstract: This study aimed to propose a procedure for the approximate and very fast Incremental Dynamic Analysis (IDA) and fragility assessment of plan-asymmetric structures using the 2DMPA (2 degrees of freedom Modal Pushover Analysis). This procedure can consider hysteretic behavior of structures such as the pinching behavior, strength loss and stiffness deterioration. Use of 2DMPA-based IDA curves for different values of mass eccentricity in an example 8-story asymmetric structure leads to good estimation for the exact IDA curves. In addition, the median of intensity measures (IM) using 2DMPA-based fragility functions has +5.0% (overestimate) and −5.2% (underestimate) approximation in the worst case. This good estimation can be used for the fast estimation of collapse in the plan-asymmetric structures. Moreover, it can be employed in the selection of a limited number of records among a large number of records to use them in the exact IDA (record selection procedure).